Evolution of electrospinning in liver tissue engineering - Vasudevan, Ashwini; Tripathi, Dinesh Mani; Sundarrajan, Subramanian S.; Venugopal, Jayarama Reddy; Ramakrishna, Seeram A.; Kaur, Savneet (MDPI, 2022)
The major goal of liver tissue engineering is to reproduce the phenotype and functions of liver cells, especially primary hepatocytes ex vivo. Several strategies have been explored in the recent past for culturing the liver cells in the most apt environment using biological scaffolds supporting hepatocyte growth and differentiation. Nanofibrous scaffolds have been widely used in the field of tissue engineering for their increased surface-to-volume ratio and increased porosity, and their close resemblance with the native tissue extracellular matrix (ECM) environment. Electrospinning is one of the most preferred techniques to produce nanofiber scaffolds. In the current review, we have discussed the various technical aspects of electrospinning that have been employed for scaffold development for different types of liver cells. We have highlighted the use of synthetic and natural electrospun polymers along with liver ECM in the fabrication of these scaffolds. We have also described novel strategies that include modifications, such as galactosylation, matrix protein incorporation, etc., in the electrospun scaffolds that have evolved to support the long-term growth and viability of the primary hepatocytes.